The Effect of Live Broadcast and Trust on Impulsive Shopping in the Purchase of H&H Skincare Products on the Tiktok Shop Application - Purwanti, Dwi; Septiani, Monica (Journal of Economics Research and Social Sciences, 2025)
This study explores how live streaming and consumer trust affect impulsive buying behavior, particularly for H&H Skincare products on TikTok Shop. Using a quantitative approach with a questionnaire distributed to 100 respondents, multiple linear regression analysis was conducted to evaluate variable relationships. The findings suggest that live streaming significantly enhances consumer engagement and increases impulsive purchases. At the same time, trust is crucial in spontaneous buying decisions. Businesses leveraging live streaming should prioritize consumer trust to boost sales and customer retention. This research contributes to digital marketing literature by examining the synergy between live streaming and trust in shaping impulsive buying behavior. Furthermore, the results offer practical implications for businesses seeking to optimize their marketing strategies on platforms like TikTok Shop. Companies can create engaging shopping experiences and increase revenue by fostering consumer trust and leveraging live streaming. The study also recommends future research to explore additional factors influencing impulsive buying in digital marketplaces.